Pengaruh Pembelajaran Berbasis e-Learning Berbantuan Geogebra terhadap Hasil Belajar Matematika Komputer dengan Kovariabel Kemampuan Spasial: Pengaruh Pembelajaran Berbasis e-Learning Berbantuan Geogebra terhadap Hasil Belajar Matematika Komputer dengan Kovariabel Kemampuan Spasial - Setiawan, I Made Dedy (UNIB Press, 2025)
Technology plays a very important role in learning activities in the digital era. In practice, learning activities in the INSTIKI class have not utilized technology optimally, especially the use of digital platforms to support mathematics learning activities. The purpose of this study was to determine the effect of e-learning-based learning assisted by Geogebra on computer mathematics learning outcomes by controlling spatial ability. This study included a quasi-experimental design with a single factor independent groups design with the use of covariate. The sample was selected by purposive sampling of 61 people who were divided into two groups. The data collection method used a spatial ability test instrument to measure students' spatial abilities, as well as a learning outcome test instrument to measure computer mathematics learning outcomes. Data analysis methods consisted of descriptive statistics, analysis prerequisite tests, and hypothesis tests. The results of the study showed that there was a significant difference in the average score of computer mathematics learning outcomes between the experimental group and the control group after spatial ability was controlled. From the results of the covariance test, the contribution of spatial ability to computer mathematics learning outcomes was 64.7%. Based on the research results, suggestions can be made including increasing the scope of teaching materials, involving a larger population, and adding control variables in similar research.